(untitled) (Tempo e Argumento, 2012)
In this article we have studied the changes and permanence in the editorial forms of written texts and visual images published in didactics books of History. We have analysed works that were produced by different authors in the 1970 and 1980 decades: Sérgio Buarque de Holanda, Antonio José Borges Hermida, Gilberto Cotrim andÁlvaro Duarte Alencar. We acknowledge that as from the 1970 decade it was established new editorial patterns for the didactic History books, which altered the ways of presentation of written texts towards the visual images. The different procedures of reading the visual images established until then, constituted editorial and scholar knowledge that served as theorical and procedural basis for the development of proposes that emerged on the didactic works produced on the decades afterwards. We expect to contribute with this study for the construction of visual images reading practices that make possible the flow, the understanding and the contextualization ofinformation that relate the usage of visual documents in the teaching of History. We look for the empowerment of the didactic procedures of reading that allows the construction, by teachers and students, of pluridimensional interpretations about the visual images as historical documents.